A Novel N-Methyltransferase in Arabidopsis Appears to Feed a Conserved Pathway for Nicotinate Detoxification among Land Plants and Is Associated with Lignin Biosynthesis . Issue 3 (22nd May 2017) - Li, Wei; Zhang, Fengxia; Wu, Ranran; Jia, Lijia; Li, Guosheng; Guo, Yalong; Liu, Cuimin; Wang, Guodong
Abstract : N-Methylated nicotinate, produced by NANMT and COMT, is a conserved nicotinate detoxification in land plants. Abstract: The Preiss-Handler pathway, which salvages nicotinate (NA ) for NAD synthesis, is an indispensable biochemical pathway in land plants. Various NA conjugations (mainly methylation and glycosylation) have been detected and have long been proposed for NA detoxification in plants. Previously, we demonstrated that NA O -glucosylation functions as a mobilizable storage form for NAD biosynthesis in the Brassicaceae. However, little is known about the functions of other NA conjugations in plants. In this study, we first found that N -methylnicotinate is a ubiquitous NA conjugation in land plants. Furthermore, we functionally identified a novel methyltransferase (At3g53140; NA N MT), which is mainly responsible for N -methylnicotinate formation, from Arabidopsis ( Arabidopsis thaliana ). We also established that trigonelline is a detoxification form of endogenous NA in plants. Combined phylogenetic analysis and enzymatic assays revealed that NA N -methylation activity was likely derived from the duplication and subfunctionalization of an ancestral caffeic acid O -methyltransferase ( COMT ) gene in the course of land plant evolution. COMT enzymes, which function in S -lignin biosynthesis, also have weak NA N MT activity. Our data suggest that NA detoxification conferred by NA N MT and COMT might have facilitated the retention of the Preiss-Handler pathway in land plants.